9C.03: THE BENEFIT FROM HEMODYNAMICALLY GUIDED ANTIHYPERTENSIVE THERAPY DEPENDS ON BASELINE BLOOD PRESSURE. (June 2015) - Krzesinski, P.; Gielerak, G.; Stanczyk, A.; Piotrowicz, K.; Skrobowski, A.
Abstract : Objective: Impedance cardiography (ICG) revealed to be useful in tailoring antihypertensive therapy to the patient's individual hemodynamic profile but little is known who benefits more from such therapeutic approach. The aim of this study was to estimate the effectiveness of ICG-guided antihypertensive therapy in 12-weeks observation with respect to baseline blood pressure (BP). Design and method: This analysis involved 272 patients with untreated AH, recruited in two randomized, prospective and controlled trials (www.nauka-polska.pl : ID227062 and ClinicalTrials.gov: NCT01996085). After baseline evaluation including office blood pressure measurement (OBPM: OSBP, ODBP, OMBP) and ambulatory blood pressure monitoring (ABPM: 24-mean_SBP, 24-mean_DBP) the subjects were randomly assigned to groups of: [GE] empiric and [HD] ICG-guided antihypertensive therapy. The effectiveness of ICG-guided therapy was evaluated after 12 weeks in subgroups derived from median of OMBP (110 mmHg) of: higher (n = 120) and lower baseline OMBP (n = 121). The comparative analysis included absolute change of BP (d_OSBP, d_ODBP, d_24-mean_SBP, d_24-mean_DBP) and percentage of patients with change of BP equal or higher than 10 mmHg (d10_OSBP, d10_ODBP, d10_24-mean_SBP, d10_24-mean_DBP). Results: In the whole study group the BP reduction in HD group was higher than in GE group: d_OSBP (18.3 vs. 14.3 mmHg; p = 0.011), d_ODBP (11.9 vs. 8.5 mmHg; p = 0.011), d_24-mean SBP (15.9 vs. 11.6 mmHg; p = 0.011) and d_24-mean SBP (10.4 vs. 8.9 mmHg; p = 0.147). However, the effect of ICG-guided therapy was significantly more pronounced in subjects with higher baseline OMBP – Table. Figure. No caption available. Conclusions: The ICG-guided therapy effects with increased BP reduction in patients with AH, especially those with higher baseline BP. The patients with advanced AH can benefit more from individual these therapeutic approach.